Performance analysis of amplify-and-forward cooperative communication systems with imperfect channel estimation - WANG Lei; CAI Yue-ming; YANG Wei-wei; TU Jia (Tongxin xuebao)
The impact of channel estimation errors on the performance for two-hop multi-relays assisted am-plify-and-forward（AF） cooperative communication systems was investigated.Closed-form expressions of the average symbol error rate,as well as the diversity gain under different channel estimation quality orders for both opportunistic re-laying（OPR） and all-participate relaying（APR） schemes were derived.Average signal-to-noise-ratio（SNR） gap ratio is investigated for the two types of cooperative communication systems,which lead to a conclusion that the OPR scheme is more susceptible to channel estimation errors than the APR scheme.Numerical results verify the theoretical analysis.